Studies towards oligodeoxynucleotide conjugates as potential photoactive antisense agents in chronic myeloid leukaemia - Crean, Conor (Trinity College (Dublin, Ireland). School of Chemistry, 2002)
The research presented in this thesis concerns the synthesis of oligodeoxynucleotide (ODN) conjugates and their use in the photochemical induction of oxidative damage to specific nucleic acid bases in a complementary ODN target strand as shown below: 5`T G A C C A T C A A T A A G G A A G A A G C C C T T C A G C G G C C3`, 3`G G T A G T T A T T C C T T C T T –sensitiser. The target strand used is an ODN model of the bcr/abl oncogenic mRNA present in chronic myeloid leukaemia (CML). As such, the aim of this research is the development of potential photoactive antisense agents, which could be used in future experiments to hinder expression of the oncogenic mRNA and be used in the development of therapeutic agents to treat CML. ODN conjugates were synthesised with photosensitising molecules, which were derivatives of a ruthenium polypyridyl complex and pteridinone derivatives. Thus, molecules were synthesised with functional groups that could be activated towards coupling with the 17-base ODN shown above. Phosphoramidite and succinimide ester coupling strategies were used to synthesise the conjugates, which were purified by electrophoresis and characterised by spectroscopic and mass spectrometric methods. The ability of the ODN conjugates to photoinduce specific damage to the target strand was assayed by gel electrophoresis experiments using 32P labeled target strands. Base sensitive modifications were induced specifically at the guanine 21 bases from the 5` end of the target using a ruthenium-ODN. A pteridinone-ODN produced such modifications at the guanines 18 and 21 bases from the 5` end of the target. The extent of base damage was visualised by autoradiography and phosphorimagery and quantified by densitometry. Investigations were also carried out using variant targets to study the effect of moving guanine 21 further away from the supposed location of the photosensitising molecules. In order to understand the mechanism of photooxidative damage, experiments were carried out using additives to investigate the role of molecular and singlet oxygen in the damage produced. A HPLC assay of the photooxidation products of 2`-deoxyguanosine in the presence of Ru(phen)3Cl2 or a pteridinone derivative was also carried out. This was used as a model to predict the photochemical behaviour of the ODN conjugates. The photooxidation products produced showed the relative contribution of competing oxidation mechanisms and thus helped to explain the photocleavage results with the ODN conjugates.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin